Facile synthesis of Cu-BDC/Poly(N-methylol acrylamide) HIPE monoliths via CO2-in-water Emulsion stabilized by metal-organic framework. (26th September 2018) - Yang, Zhen; Cao, Liqin; Li, Jing; Lin, Jiangli; Wang, Jide
Abstract: Macroporous poly( N -methylol acrylamide)–high internal phase emulsion [poly(NMA)HIPE] composite monoliths were prepared by carbon dioxide-in-water (CO2 /W) emulsions using metal-organic framework (MOF) Cu-BDC (BDC = 1, 4-dicarboxybenzene) as stabilizer. The composite monoliths were characterized using XRD, SEM, EDS-mapping, FT-IR, TG, and mercury injection methods. Increasing the internal phase fraction would lead to the decrease of monolith density and the increase of void size, and it is favorable for the formation of macroporous interconnected structure with low density and porosities up to 81.6%. The mechanical properties of the Cu-BDC/poly(NMA)HIPE and Cu-BDC removal were also evaluated. The composite polyHIPEs exhibited high antibacterial activity against Escherichia coli . The presented approach facilitated the clean manufacture of open-celled MOF based scaffolds in a one-pot process with porosity of up to 82%. Graphical abstract: Image 1 Highlights: Composite HIPE Monoliths obtained via C/W HIPE Emulsions. The volatile organic solvent is avoided. Exhibited a high compressive stress of 2.2 MPa and 91.5% strain. Exhibited antibacterial activity against Escherichia coli. A coordination polymer uniformly dispersed in PolyHIPE.